Risk and reward: Balancing safety and maximizing lung donors during the COVID-19 pandemic - La Hoz, Ricardo M. (Am J Transplant, 2021)
In response to Kaul et al.’s article (page 2885), the editorialists recommend testing lower respiratory tract samples from potential deceased lung donors for SARS-CoV-2 to mitigate the risk of donor derived disease.